Interpretation of the Verse of Compulsion from Surat Al-Nahl: An Analytical Study - Abdul Rahman, Ibtihaj Radi (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: This research explores the ruling of uttering words of apostatsy and the relevant factors, such as willingness, coercion, dispensation, and obligation. It also investigates what actions are considered permissible when coercion is involved with examples of this in our contemporary reality. Methods: The study uses inductive and analytical approaches to examine a verse from Surat al-Nahl, which is referred to here as “the verse of forced opostasy” that is pertinent to the topic of the current study. The deductive approach was also used to present the relevant statements of Fuqaha (jurists), highlighting the most suitable and appropriate in dealing with legally competent, obligated Muslims. Results: According to the study, Muslims may face difficult situations that prompt them to say or do things that do not rise to the level of disbelief or to act out of character. In Palestine, Iraq, and elsewhere, people are tortured in prisons and detention centers or threatened with death at military checkpoints. Thus, if forced to comply with an adversary's demands, one must evaluate the situation and decide. Conclusions: The "forced apostasy verse" is relevant to modern times since Muslims can be coerced into saying or doing things that contradict their faith, such as being threatened to be crucified or bending the knee to a cross. In such cases and to avoid death, Muslims may condone acts of disbelief, such as the desecration of the Quran.